ANALISIS EFEKTIVITAS APLIKASI SISTEM INFORMASI ASET POLRI MENGGUNAKAN METODE TECHNOLOGY ACCAPTANCE MODEL PADA BIRO SARPRAS POLDA JAMBI - Mintaria, Mintaria; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
In the development of information technology in the goverment and the prive sectors keep on developinga system of information based application. But in fact, there are a lot of application of this systeminformation can not be used effectively buy user. As in the implementantion of property’s of the systeminformation on the facilites and infrastructure office Polda Jambi is still less effective to use. It makes theresearcher need to research about the effectiveness of application of Polri propertys system of informationwhich is applied in Polda Jambi’s office of facilities and infsdtructure (Biro Sarpras Polda Jambi) basedon the reasercher’s research used Technology Accaptance Model (TAM) as a method, it found that thereare 100 respondents filled the questionnaire showed that all of them do not really understand, feel doubtand have no willingness in using that application. So, it makes this application can not be applideffectively